Trastuzumab-Associated Flagellate Erythema: Report in a Woman with Metastatic Breast Cancer and Review of Antineoplastic Therapy-Induced Flagellate Dermatoses. Issue 4 (December 2015) - Cohen, Philip
Abstract Introduction Flagellate erythema presents as erythematous, individual and intermingled, linear streaks in a whiplash-like pattern. Several conditions, including antineoplastic agents, have been associated with flagellate erythema. A woman with metastatic breast cancer who developed flagellate erythema after receiving trastuzumab is described and the features of flagellate erythema associated with other antineoplastic agents are reviewed. Methods PubMed was used to search the following terms, separately and in combination: agent, antineoplastic, bendamustine, bleomycin, breast, cancer, chemotherapy, dermatitis, dermatosis, docetaxel, erythema, flagellate, Herceptin, pigmentation, peplomycin, therapy, and trastuzumab. All papers were reviewed and relevant manuscripts, along with their reference citations, were evaluated. Results The woman's pruritus and skin lesions promptly resolved after treatment with corticosteroids (oral and topical) and antihistamines (oral); premedication with dexamethasone prior to each subsequent trastuzumab treatment prevented recurrence of flagellate erythema. Chemotherapy-induced flagellate erythema was initially described in oncology patients who received bleomycin. In addition to trastuzumab, other antineoplastic agents that have been associated with the development of flagellate erythema include bendamustine, docetaxel, and peplomycin. Conclusion Cutaneous adverse events to trastuzumab are uncommon. However, flagellate erythema should be added to the potential side effects of trastuzumab. In addition, trastuzumab should be added to the list of antineoplastic agents that may be associated with flagellate erythema.